STUDI KORELASI UMUR KEHAMILAN DENGAN KEJADIAN NYERI PUNGGUNG IBU HAMIL - Ulfah, Mariah; Wirakhmi, Ikit Netra (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Back pain is common in pregnancy. The experience of back pain is often experienced by pregnant women about 24% -90% during pregnancy (JosPt, 2014). There are several factors that contribute to these symptoms during pregnancy including pelvic changes as well as changes in loading due to increasing gestational age (Sabino, Jennifer 2008). Puskesmas Kembaran I is a health center that runs pregnant women's classes. Based on a preliminary study conducted in the class of pregnant women in Purbadana and Kembaran villages in March 2016, of 31 pregnant women stated that 65% had back pain, which was quite disturbing to patients, often using pharmacologic treatment by taking calcium or using oil white wood. Based on the phenomenon, the authors are interested to know to know the relationship between pregnancy age and body mass index of pregnant women with low back pain in pregnant women. Problem formulation is as follows: how the correlation of gestational age with low back pain in pregnant women? The purpose of this study is to know the correlation of gestational age with lower back pain in pregnant women. Keywords: age of pregnancy, back pain